A new Toerpenola László, Ronkay & Witt, 2010 (Lepidoptera, Nolidae) from Laos with a checklist of the genus - Cha, Yeong-Bin; Bayarsaikhan, Ulziijargal; Bae, Yang-Seop; Kim, Sora (Zootaxa, 2025)
A new Toerpenola László, Ronkay & Witt, 2010 species, T. laosiana Cha sp. nov. is described with illustrations of both sexes. A checklist of the genus and some taxonomic discussions are also presented.